DETERMINING THE DIAGNOSTIC SIGNIFICANCE OF SCALES FOR ASSESSING DISEASE SEVERITY IN RESTLESS LEGS SYNDROME ACCOMPANIED BY NEUROLOGICAL DISORDERS - Umida G. Yodgarova (Central Asian Journal of Medicine, 2025)
The study involved 42 patients with symptomatic restless legs syndrome (RLS) associated with neurological diseases. The severity of disease symptoms in all patients was assessed using the Augmentation Severity Rating Scale (ASRS) and the Johns Hopkins Restless Legs Severity Scale (JHRLSS). The International Restless Legs Syndrome Rating Scale (IRLS), known for its high sensitivity, was used to evaluate the effectiveness of the scales in determining the severity of RLS symptoms. For mild symptoms, the IRLS and ASRS scales demonstrated equal effectiveness, identifying symptoms in 10 (90.9%) patients each. The JHRLS scale identified symptoms in 6 (54.5%) patients, which is 1.67 times lower compared to the IRLS and ASRS scales. Moderate symptoms were detected in 1 (9.09%) patient using the IRLS scale and in 2 (18.1%) patients using the JHRLS scale, indicating 2 times greater sensitivity of the latter compared to the IRLS. The ASRS scale failed to detect moderate symptoms, indicating its low sensitivity. The ASRS scale identified severe symptoms in 1 (9.09%) patient, while the IRLS and JHRLS scales did not detect symptoms of this severity. Extremely severe symptoms were equally identified using the JHRLS and ASRS scales in 1 (10.0%) patient each, while the IRLS scale did not register such symptoms.